Probe Positioning for the Exhaust Emissions Measurements. (2017) - Jasiński, Remigiusz; Markowski, Jaroslaw; Pielecha, Jacek
Abstract: Emission of harmful compounds in the exhaust gases depends on the operating conditions of the engine and its technical condition. Therefore, the legislative activity is focused on the introduction of new diagnostic and research procedures. The preferred method is using probes with plurality of holes for multi-gas sampling from the entire cross-section of exhaust stream. This method appears to vitiated by an error caused by averaging dilution and sampling gas from the very beginning of the measurement path. The results of measurements contained in the article are related to changes in the concentration of harmful substances in exhaust gases depending on the distance from the axis of the jet. In the article the disadvantages of this the methods were highlighted and the single-point measurement method was proposed.